2022
DOI: 10.1002/star.202200090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nano‐Titanium Dioxide andMentha piperitaEssential Oil on Physicochemical, Mechanical, and Optical Properties of Cassava Starch Film

Abstract: The objective of this study is to investigate the synergistic effects of nano titanium dioxide (TiO 2 -N) and Mentha piperita essential oil (MEO) on cassava starch film characteristics. Cassava starch films with TiO 2 -N (1%, 3%, and 5% of dried starch) and MEO (1%, 2%, and 3% of dried starch) are prepared by a casting method. Physicochemical, mechanical, barrier, and optical properties of the films are evaluated. The moisture content, solubility, water absorption capacity, water vapor permeability, and transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Also, its high refractive index leads to diffuse reflection of light, which justifies the reduced transparency of films. 31,62 Wavelengths between 200 and 400 nm showed the best indices, considering that the transmittance values did not exceed 0.5%, as observed in Table 5. In terms of the visible region, there was a wide reduction in transmissibility, from 89.54% for the FA film to 39.81% for the FAN/2DT film.…”
Section: Morphological Evaluation Of Filmsmentioning
confidence: 64%
See 2 more Smart Citations
“…Also, its high refractive index leads to diffuse reflection of light, which justifies the reduced transparency of films. 31,62 Wavelengths between 200 and 400 nm showed the best indices, considering that the transmittance values did not exceed 0.5%, as observed in Table 5. In terms of the visible region, there was a wide reduction in transmissibility, from 89.54% for the FA film to 39.81% for the FAN/2DT film.…”
Section: Morphological Evaluation Of Filmsmentioning
confidence: 64%
“…Oleyaei et al 43 found in starch films with addition of 0, 0.5, 1, and 2 wt% TiO 2 opacity from 0.32 to 6.70 nm/mm with transmittance of 0.02% (UVC, UVB and UVA) and 5.61% (Visible) at the highest TiO 2 concentration. Noorian et al 62 observed in films of starch/TiO 2 and essential oil of Mentha piperita , a significant reduction in transmittance between the control sample (starch) and the other films containing 1, 3, and 5 wt% of TiO 2 . Yousefi et al 46 found better opacity results with the incorporation of 1, 2, and 4 wt% TiO 2 , with values of 1.558, 1.835, and 3.45 nn/mm, respectively, in starch, montmorillonite, and TiO 2 films.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2022) found similar behavior in cassava starch‐based films with 1 to 5 wt.% of TiO 2 nanoparticles prepared by casting and they also showed improvements in the mechanical properties. [ 28 ] These authors demonstrated that the employment of 1 wt.% of the nanofiller was high enough for enhancing the film's properties. This concentration is also recognized as safe (GRAS) by FAO and the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is a natural, biodegradable, available, abundant, and hydrophilic polymer whose main sources are cereals, legumes, tubers, and roots. [ 12 ] Starch has the ability to improve viscosity and texture, retain moisture, binding, gelling, homogeneity of the food products. Therefore, starches from different sources are widely used in the food industry.…”
Section: Introductionmentioning
confidence: 99%